2012
DOI: 10.1002/ajmg.b.32014
|View full text |Cite
|
Sign up to set email alerts
|

Tests of linkage and allelic association between markers in the 1p36 PRKCZ (Protein Kinase C Zeta) gene region and bipolar affective disorder

Abstract: Three linkage studies of families with multiple cases of bipolar disorder and/or unipolar affective disorder have confirmed the involvement of the chromosome 1p36 region in the etiology of affective disorders with LOD scores of 2.7, 3.6, and 3.97. We investigated the protein kinase C zeta gene (PRKCZ) as a susceptibility locus for bipolar disorder because it is highly brain expressed and is localized close to the marker D1S243 which was linked to affective disorder in a single large UCL bipolar disorder family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Genetic studies have also implicated PKC in BD [141,142,143]. In the following section, we will briefly discuss putative gene candidates involving activator protein 1 (AP-1), GSK-3beta, DAG kinase eta (DGKeta), and PKC interacting protein/histidine triad nucleotide binding protein 1 (PKCI/HINT1), that highlight putative genetic mechanisms underlying BD.…”
Section: Geneticsmentioning
confidence: 99%
“…Genetic studies have also implicated PKC in BD [141,142,143]. In the following section, we will briefly discuss putative gene candidates involving activator protein 1 (AP-1), GSK-3beta, DAG kinase eta (DGKeta), and PKC interacting protein/histidine triad nucleotide binding protein 1 (PKCI/HINT1), that highlight putative genetic mechanisms underlying BD.…”
Section: Geneticsmentioning
confidence: 99%
“…4 .B. These regions include the following cytobands: murine 4qE, homologous to human 1p36, implicated in BPD in two studies with linkage scores of 3.97 [60] and 3.1 [61] and a region in which SNPs predict BPD susceptibility [62] ; murine 5qF, homologous to human 12q24, implicated in BPD in multiple studies with linkage scores of 4.91 [63] , 3.63 [64] , 3.37 [65] , 2.8 [61] , and 2.08 [66] and a region in which SNPs and allele variants predict BPD susceptibility [44] , [46] , [67] ; 8qE1, homologous to human 16q24, implicated in BPD in two studies with linkage scores of 3.51 [68] and 2.29 [69] ; murine 11qE2, homologous to human 17q25, implicated in BPD in five studies with linkage scores of 3.11 [70] , 2.4 [71] , 2.4 [72] , 2.1 [73] , and 2.08 [74] ; murine 13qA3 and 17qA3-17qB1, two cytobands with homology to human 6p21–22, implicated in BPD in multiple studies with linkage scores of 3.19 [68] , 2.60 [75] , 2.26 [72] , and 1.91 [69] ; murine 14qA1, homologous to human 3p14, implicated in BPD in two studies with linkage scores of 3.51 [76] and 2.31 [77] ; and murine 16qB2–B3, homologous to human 3q29, implicated in BPD in two studies with linkage scores of 3.74 [78] and 2.0 [61] . Additional enriched genome regions showing weaker previous relationships to BPD included: murine 2qE, homologous to human 11p13, implicated in BPD in one study with a linkage score of 1.95 [79] and a region in which SNPs and allele variants predict BPD susceptibility [80] , [81] ; murine 8qB2–B3.1, homologous to human 4q34, implicated in BPD in a study with a linkage score of 3.28 [82] ; murine 8qB3.3 and 9qA3, homologous to human 19p13, implicated in BPD in three studies with linkage scores of 2.37 [83] , 1.8 [66] , and 1.55 [84] ; and 15qE3, homologous to 22q13, implicated in BPD in o...…”
Section: Resultsmentioning
confidence: 99%
“…PRKCZ in cord blood T cells has been associated with allergy risk in infants and it has been reported that gender differences affect susceptibility to the development of hypersensitivity reactions [ 33 , 34 ]. The PRKCZ gene has also been linked to development of bipolar disorder [ 35 ] in line with the increased risk of psychiatric illness such as bipolar disorder in males compared to females [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%